Evaluation of Electromyography and Muscle Contraction in the Use of Myofunctional Appliances: A Systematic Review (Journal of Pharmaceutical Negative Results, 2022)
Background: Electromyography (EMG) is the study of muscle function through the analysis of electrical signals generated spontaneously or during voluntary contractions. EMG plays an important role in the diagnosis of facial muscles during orthodontic treatment related to neuromuscular involvement and facial pain associated with the use of myofunctional appliances. Orofacial muscle function plays an important role in the formation of an ideal occlusion during childhood growth. Orofacial muscles that can affect the development of dental occlusion are the tongue, masseter and buccinator muscles, and orbicularis oris. Triangular Force Concept is the concept of balance between the three muscles. Early detection of the imbalance of the three muscles can prevent malocclusion in children. One of the treatment for malocclusion in children with orthodontic problems is the use of myofunctional appliances, both removable and fixed. Removable myofunctional appliances that can be used such as activators, twin- blocks, bionators, Frankel function regulators and sanders. While fixed myofunctional appliances that can be used such as Herbst, Jasper jumper and RME. Objectives: To systematically review electromyography and its relation to muscle contraction in the use of myofunctional appliances as a treatment for malocclusion in children. Methods: Data collection was carried out by searching literature on article search sites, namely Pubmed, Cochrane, Wiley, Google Scholar and Science direct which were published from 2016 to 2021, the search was carried out in March 2016 - May 2021. Data search was carried out systematically using keywords. Electromyography, Muscle contractions, Myofunctional appliances, Children and adolescents.Results: After eliminating duplicate articles, the title and abstract of each article were analyzed in 441 articles which were excluded from 408 articles. The full-text articles in the remaining 33 articles were re-analyzed and 29 articles were excluded. The complete text of the journal article and fulfills the eligibility is 4 articles. Conclusion: Surface electromyography is a useful tool for monitoring muscle activity. After functional therapy resulted in changes in masticatory muscle activity. Myofunctional appliances that promote the correction of malocclusion are capable of causing neuromuscular changes which in turn result in muscle balance and harmonious jaw development.